Hubungan Usia, Lamanya Pemakaian Suntik Progestin dengan Kejadian Hipertensi pada Akseptor KB Suntik Progestin - Tri Setiowati; Sri Yuniarti,S.Psi.,SST.,MKM, Bdn.; Amelya Hidayat, Intan (JURNAL KESEHATAN KARTIKA, 2025)
Background: The use of injectable hormonal contraceptives, especially those based on progestin, is the most popular method of family planning in Indonesia. However, the long-term side effect of increased blood pressure remains a major concern as it can increase the risk of hypertension. Hypertension remains a serious health problem, including among women of reproductive age who use hormonal contraceptives. There is still limited research that specifically assesses whether age and duration of progestin injection use directly contribute to the incidence of hypertension in FP acceptors. Objective: This study aims to determine the relationship between age and duration of progestin injection use and the incidence of hypertension in progestin injection FP acceptors at the Independent Midwife Practice (TPMB) A in Karawang Regency in 2024. Methods: This study is a quantitative study with a cross-sectional design. The population consisted of all progestin injection contraceptive users at TPMB A in 2023, totaling 131 people, and the entire population was sampled using total sampling technique. Secondary data were obtained from the contraceptive register. Data analysis was performed using univariate and bivariate analysis with the Chi-Square test at a significance level of 0.05. Results: Most respondents were aged 18–40 years (74.8%), had been using progestin injections for ≥2 years (63.3%), and experienced hypertension in 40.5% of cases. The Chi-Square test results showed a significant relationship between age and the incidence of hypertension (p=0.000; OR=53.545) and between the duration of progestin injection use and the incidence of hypertension (p=0.000; OR=22.727). Conclusion: Age ≥40 years and duration of progestin injection use ≥2 years are significantly associated with an increased incidence of hypertension. It is recommended that midwives provide education and regular blood pressure monitoring for long-term progestin injection users.